In vivo delivery of a fluorescent FPR2/ALX-targeted probe using focused ultrasound and microbubbles to image activated microglia - Morse,SV; Boltersdorf,T; Chan,TG; Gavins,FNE; Choi,JJ; Long,NJ (RSC Chemical Biology, 2020)
To image activated microglia, a small-molecule FPR2/ALX-targeted fluorescent probe was locally delivered into the brain using focused ultrasound and microbubbles. The probe did not co-localise with neurons or astrocytes but accumulated in activated microglia, making this a potential imaging tool for future drug discovery programs focused on neurological disorders.